PENGARUH SUHU AKTIVASI TERHADAP SIFAT FISIS DAN ELEKTROKIMIA ELEKTRODA SUPERKAPASITOR DARI LIMBAH DAUN AKASIA (Acacia mangium Wild) - Kristin Natalia; Erman Taer (Universitas Riau, 2019)
The carbon electrode from acacia leaves (Acacia mangium Wild) for supercapacitor cell has been fabricated with physical activation temperature variations of 800oC, 850oC, and 900oC for the AK800, AK850 and AK900 samples respectively. Carbon electrodes were carbonized at a temperature of 600oC followed by physical activation in CO2 gas atmosphere. The KOH is use as an activating agent. The results of physical properties characterization show the higher physical activation temperature cause lower density data and smaller pore size of the particles. The EDX data shows an increasing in the carbon content. The best specific capacitance was found in AK900 as high as 76 g F-1 and the lowest specific capacitance is found in AK800 as high as 12,4 g F-1. Specific capacitance increases with increasing physical activation temperature.